Assessment of Morphological Changes in Breast Cancer Cells Following X-Ray Radiation Utilizing Digital Holographic Microscopy - Zeinab Hormozi-Moghaddam; Seyedeh Mona Taheri; Reza Paydar; Ali Neshasteh-Riz; Vahideh Farzam Rad; Mohadeseh Shaghaghi (Frontiers in Biomedical Technologies)
Purpose: Digital holographic microscopy, being a label-free and entirely non-invasive technique, proficiently facilitates the quantitative assessment of morphological alterations in living cells. The primary objective of this investigation is to scrutinize the capability of a digital holographic microscope in assessing the morphological transformations of cancer cells exposed to X-ray radiation.